2012
DOI: 10.1159/000336554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Elevation above Sea Level on Blood Oxygen Saturation in Healthy Young Adults

Abstract: Background: Arterial hemoglobin oxygen saturation (SaO2) decreases at an altitude of >1,500 m. There are no reports on normal SaO2 at altitudes between 0 and 1,500 m. The clinical significance of decreased SaO2 at such altitudes is unclear. Objective: To test the hypothesis that in healthy volunteers normal SaO2 at moderate altitude (MA; 725 m) is lower than that at almost sea level (SL; 43 m). Methods: SaO2 was measured by transcutaneous pulse oximetry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
(31 reference statements)
2
12
0
1
Order By: Relevance
“…Prior studies have evaluated the way oxygen saturation varies by elevation. 32,33 In the future, use of oxygen saturation prediction models or pressure altitude could be used rather than topographical elevation to better model the underlying constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have evaluated the way oxygen saturation varies by elevation. 32,33 In the future, use of oxygen saturation prediction models or pressure altitude could be used rather than topographical elevation to better model the underlying constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors are known to influence the SpO 2 values. Among them: age, body temperature, blood pH, partial CO 2 and O 2 pressures, altitude and barometric pressure . It is not known whether sex also influences SpO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them: age, body temperature, blood pH, partial CO 2 and O 2 pressures, altitude and barometric pressure. [2][3][4] It is not known whether sex also influences SpO 2 . In recent years there has been a growing interest in studying differences between sexes, both from a physiological and a clinical perspective.…”
Section: Introductionmentioning
confidence: 99%
“…A final limitation is that the oxygen saturation was not measured in the sham group (SH), as we did not expect to find significant changes in SH oxygen saturation at such low simulated altitude. Recent studies have shown that exposure to low altitudes result in small, clinically insignificant decreases (0.42%) in oxygen saturations (Goldberg et al, 2012). Even if a decrease occurred in oxygen saturation in SH subjects, it would have minimized, rather than exaggerate, the differences between the groups.…”
Section: Limitationsmentioning
confidence: 99%